PENERAPAN TEKNOLOGI POMPA HIDRAM DAN AIR SIAP MINUM UNTUK PEMENUHAN KEBUTUHAN AIR DI PERMUKIMAN - Wiwin Widiastuti; Dimas Pamungkas Pradoto; Sudianto Sudianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
The applied of Hydraulic Ramp Pump Technology and Drinking Water Technology aim to develop the appropriate technologies to fulfill the needs of water supply for residents in Kotayasa Village Sumbang Sub-district Banyumas Regency and Pojok Village Mojogedang Sub-district Karanganyar Regency. The development result shows that Hydraulic Ramp Pump Technology able to provide a solution to oververcome the problems of lifting water from the low plains to higher ground without using either electrical energy or fuels in Kotayasa Village Sumbang Sub-district Banyumas Regency. Clean water and drinking water technology able to provide solutions for fulfill water needs in densely populated areas of Pojok Village Mojogedang Sub-district Karanganyar Regency.